Social mobility of Orang Asli: a conceptual paper / Farah Adilla Ab Rahman …[et al.] - Ab Rahman, Farah Adilla; Mohamed Harith, Nor Hafizah; Zainuddin, Azizan; Mohd Zain, Zarina (Universiti Teknologi MARA, 2021)
Social mobility exists because of the causes and effects of collective or individual movements arising from changes in the social system (Aldridge, 2001). In 2020, the World Economic Forum produced Global Social Mobility Report that placed Malaysia at Number 43 indicating that there are decreased opportunities for people in health care, education, access to technology, working conditions and social protection (The Global Social, Mobility Report, 2020). Furthermore, social mobility does affect the indigenous people in terms of their employment, education and risk of exclusion (United Nations, 2016). The 2030 Agenda for Sustainable Development has the potential to be transformative for indigenous people if its implementation respects these principles of equality and participation (United Nations, 2017). To achieve the SDGs in Malaysia, the government is committed to increase the socio-economic well-being of the indigenous people. Moreover, the Malaysian government has planned several development programmed such as the New Economic Policy, Structured Placement Program and a few more, to improve the social mobility of the indigenous people (Wee, Maryati, & Mohd Nur Syufaat, 2013. As a result, the focus of this conceptual paper will be on a discussion of the lack of literature related to the social mobility of Orang Asli in Malaysia, factors influencing social mobility, and possible future studies in social mobility concerning indigenous people in Malaysia.